Complex Nature of Neural Tube Defects: A Regional Experience - Emrah Turhan; Fusun G Varol; Hakan Gurkan; Cenk N. Sayin (Medical Network, 2018)
Objective: The underlying gene-environment interaction of fetal neural tube defects is affected by several factors including geography, ethnicity and time. Local features of fetal neural tube defects were described. Study Design: A prospective cohort study of 48 fetal neural tube defects in a single tertiary medical center at the northwestern region of Turkey (2013-2015) was done via ultrasound, magnetic resonance imaging (MRI), conventional karyotyping, maternal methylenetetrahydrofolate reductase c.677C>T (rs1801133) single-nucleotide polymorphism and maternal serum levels of folic acid, vitamin B12 and zinc. For comparison of means, a Student's T-Test was used. Results: The prevalence of neural tube defects was 11.4 per 10000 births (48/42000) in northwestern Turkey. The defects on the cranium (n=23; 47.9%) and spine (n=25; 52.1%) were ultrasonographically detected. MRI did not give additional benefit over the ultrasonography. The ratio of associated anomalies in neural tube defect group was 25%. Two fetal neural tube defects with Down syndrome were remarkable. The rate of homozygous methylenetetrahydrofolate reductase c.677C > T SNPs among the mothers of neural tube defect fetuses (n=20) was 15%. Comparing with gestationally matched healthy pregnancies, although maternal BMIs and periconceptional folate intake of neural tube defect group were significantly different, maternal serum folic acid, vitamin B12 and zinc levels were similar. Conclusion: The northwestern region appeared to be a relatively low prevalence area of Turkey for fetal neural tube defects. Any association with maternal serum folic acid, vitamin B12 and zinc levels could not be shown in this region.